2016
DOI: 10.1016/j.nicl.2016.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Repeated acupuncture treatments modulate amygdala resting state functional connectivity of depressive patients

Abstract: As a widely-applied alternative therapy, acupuncture is gaining popularity in Western society. One challenge that remains, however, is incorporating it into mainstream medicine. One solution is to combine acupuncture with other conventional, mainstream treatments. In this study, we investigated the combination effect of acupuncture and the antidepressant fluoxetine, as well as its underlying mechanism using resting state functional connectivity (rsFC) in patients with major depressive disorders.Forty-six femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 105 publications
2
63
0
Order By: Relevance
“…In our previous study, we reported how acupuncture plus fluoxetine treatment modulates the rsFC of the amygdala related network (Wang et al, 2016). In this manuscript, we focus on how acupuncture modulates the rsFC of the extended corticostriatal network using a seed-to-whole-brain method, which has never been reported before.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we reported how acupuncture plus fluoxetine treatment modulates the rsFC of the amygdala related network (Wang et al, 2016). In this manuscript, we focus on how acupuncture modulates the rsFC of the extended corticostriatal network using a seed-to-whole-brain method, which has never been reported before.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, accumulating evidence has indicated that acupuncture combined with antidepressant medication is more effective than antidepressants alone, and is safe, well-tolerated, and has an early onset of action (Chan et al, 2015; Wang et al, 2016; Zhang, Yang, & Zhong, 2009), which embodies the potential of combining acupuncture and pharmacological treatments for depression.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneity: chi 2 = 11.20, df = 9 (P = 0.26); I 2 = 20% Test for overall effect: Z = 7.92 (P < 0.00001) Heterogeneity: chi 2 = 20.44, df = 13 (P = 0.08); I 2 = 36% Test for overall effect: Z = 8.21 (P < 0.00001) Test for subgroup differences: chi 2 =5.94, df = 1 (P = 0.01); I 2 = 83.2% Evidence-Based Complementary and Alternative Medicine [49][50][51][52]. It is generally believed that the LPNN is related to sleep and emotions.…”
Section: Subtotal (95% Ci)mentioning
confidence: 99%
“…These researchers concluded that the additional benefit of acupuncture was achieved via its positive regulatory influence on the limbic system, particularly the amygdala and anterior cingulate cortex. 15 Benefits derived from auricular amygdala acupuncture are consistent, precise, and frequently extraordinary. Patients from the current author's clinical practice are well-informed regarding the clinical significance amygdala function and the rationale for addressing it through the auricular-acupuncture microsystem.…”
Section: Psychiatric Applicationsmentioning
confidence: 99%